Radiological description of the osteology of Goeldi’s marmoset (Callimico goeldii) kept in captivity - Grandez R., Ricardo (2018)
The objective of the study was to radiologically describe the osteology of the Goeldi’s marmoset (Callimico goeldii). Five individuals reared in captivity, in apparently good health, of the Huachipa Zoological Park (Lima, Peru) were used. They underwent a previous clinical examination to verify the good state of health. The animals were anesthetized and positioned in dorsal and lateral decubitus for radiological evaluation. Likewise, views of the appendicular skeleton were obtained and a record of different exposure values was made to determine their optimum values. The results showed that the optimal exposure values to obtain radiographic images in this species for head and thorax-abdomen were dorso-ventral and lateral views of 50Kv, 20 mA, 0.03 s and for the extremities mediallateral view of 50 kV, 20 mA, 0.02 s. It was evidenced that the tibia and the fibula are fused in their lower third and have a distal curvature, the pelvis has its maximum width at the level of the iliopubic eminences, and the proportions of the four limbs of this species are less than proportions of other Neotropical primates. From the present study it can be concluded that there are morphological differences at the level of the pelvis and hind limbs in relation to other primate species, possibly due to the locomotion pattern by vertical jumps in this species.